Chronic Ethanol Decreases the Left Ventricular Cardiac Performance - VMB, Camargo; FC, Damatto; VC, Fioravante; AR, Godoi; EG, Stoppa; MP, Okoshi; K, Okoshi; JRA, Miranda; FE, Martinez (Journal of Cardiology and Cardiovascular Medicine, 2024)
Introduction: Spaced fiber bundles, less evident cell striations, deposition of collagen fiber bundles, and increased presence of fibroblasts in the cardiac tissue of rats that voluntarily and chronically ingested ethanol were observed by our research group. In addition, we observed increased proliferation and cell death of cardiomyocytes. To find out whether these changes lead to impaired heart functionality, some clinical tests were performed. Aim: to investigate whether chronic ethanol decreases the left ventricular performance assessed by exercise testing, electrocardiogram, and echocardiogram of male and female UChB strain rats. Material and methods: ten adult males and ten adult females, Wistar strain rats, named UChB (University of Chile), spontaneous high ethanol drinkers (consumption greater than 2 g ethanol / Kg body weight/day), and ten male UChB rats and ten adults female UChB rats, not exposed to ethanol, UChBC rats (controls) were used. Cardiac performance was evaluated by the stress test, electrocardiogram, and echocardiogram. Results: Exposed females showed ventricular morphological changes in the heart. The exposed females and males had the highest heart relative weight with females being larger than males. The exposed females showed altered electrocardiogram and echocardiogram. Conclusion: Chronic ethanol decreases the left ventricular cardiac performance in rats. Females are more sensitive to changes in cardiac electrical conduction.